Effect of calcination temperature on the electrochemical properties of nickel-rich LiNi0.76Mn0.14Co0.10O2 cathodes for lithium-ion batteries - Zheng, Jianming; Yan, Pengfei; Estevez, Luis; Wang, Chongmin; Zhang, Ji-Guang (Nano energy, 2018)
High energy density, nickel (Ni)-rich, layered LiNixMnyCozO2 (NMC, x ≥ 0.6) materials are promising cathodes for lithium-ion batteries. However, several technical challenges, such as fast capacity fading and high voltage instability, hinder their large-scale application. Herein, we identified an optimum calcining temperature range for the Ni-rich cathode LiNi0.76Mn0.14Co0.10O2 (NMC76). NMC76 calcined at 750–775 °C exhibits a high discharge capacity (~215 mAh g−1 when charged to 4.5 V) and retains ca. 79% of its initial capacity after 200 cycles. It also exhibits an excellent high-rate capability, delivering a capacity of more than 160 mAh g−1 even at a 10 C rate. The high performance of NMC76 is directly related to the optimized size of its primary particles (100–300 nm) (which constitute the spherical secondary particles of >10 µm) and cation mixing. Higher calcination temperature (≥800 °C) leads to rapid increase of primary particle size, poor cycling stability, and inferior rate capability of NMC76 due to severe micro-strain and -crack formation upon repeated lithium-ion de/intercalations. Therefore, NMC76 calcined at 750–775 °C is a very good candidate for the next generation of Li ion batteries. [Display omitted] •Temperatures of 750–775 °C are optimum for calcining Ni-rich LiNi0.76Mn0.14Co0.10O2.•The primary particle size of Ni-rich cathodes was controlled by the calcination temperature.•The size of primary particles showed significant effects on the structural integrity of secondary particles.•Ni-rich materials constructed with primary particles of 100–300 nm exhibited the best electrochemical performance.